Orientalisme dan Penerjemahan Al-Qur’an - Egi Sukma Baihaki (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
The Qur'an is believed by Muslims as the last holy book, the revelation of God, and the greatest miracle possessed by the Prophet. The Qur'an contains values, insights, and science, also contains laws that serve as guidelines for human life. Translation of the Qur'an is one effort to capture the message of the Qur'an. The act was also carried out by Orientalists who translated the Qur'an in different languages for various reasons. Competition, suspicion, and hatred and elements of power cannot be separated from the history of translation of the Qur'an by the Orientalists. Nevertheless, the paradigm over time began to shift, and made some European intellectuals soft and friendly with Islam, although there are still others who continue to follow in the footsteps of their predecessors.